Rancang Bangun Prototipe Rangkaian Penerima Sistem Daya Tanpa Kabel - Bimantara, Fredi, Aris Budiman, S.T., M.T (2017)
Technological developments in electronic devices is faster and more in widespread use now. it needs electrical power and cable as a mean of power transfer. Uses of wireless technologies are now in developing. So as to ease of use while wearing an electronic device that can transfer electric power wirelessly can certainly ease when used. The purpose of this research is to create a prototype of a wireless electric power transfer receiver. The method used in this research include the study of literature, data collection, design the device, device-making, further testing using 16 V DC / 5A power supply. Transmitter coil uses a copper pipe with the cross-sectional area of 28,26 mm². While at the receiver using copper cable 1,5 mm² small led then compared with 1 watt led receiver using copper cable 1,5 mm² and 3 watt led receiver using copper cable 2,5 mm² at a distance of 1-21 cm. The results of this test has the highest efficiency of 91.92% at a distance of 1 cm when under a 3 watt led lamp, the greater the distance will further lower the efficiency. Transfers can only be a maximum power at a distance of 21 cm when under the LED lights. Keywords: No cable, distance, cross-sectional area